Schöne neue Medienwelt: Wie die digitale Revolution ihre Kinder frisst - Heinze, Achim (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
"Brave New Media World" educates people about media addiction and digitally triggered diseases. After all, the current digital revolution represents a similarly large turning point in human history as industrialization once did. What was initially sold as liberal and harmless consumer pleasure has now gradually turned into superficial politainment, radical depictions of violence, monochrome opinion-making, anticipatory political correctness and low-stimulus edutainment. Ruthless digital Darwinism was elevated to the new ideal. Achim Heinze presents a book that provides both theoretical foundations and uses practical examples to show what successful media literacy looks like in concrete terms.